(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Mitochondrial DNA hypervariable regions II of control region were sequenced from 139 random healthy unrelated individuals ethnic of Iraqi population in Basrah city. The aim of this study was to detect and classify the mtDNA haplotypes into mtDNA haplogroups will be better in applications of the forensic genetics and will determine the history of the Iraqi Population The variation in sequence within the D-loop control region was analyzed for the haplogroups composition which displayed a high haplogroups frequency. H, J, U, B, N and R (25%, 12%,12%, 7%, 5% and 5%, respectively, Moderate Haplogroups Frequency L, T and W was (3%) HV, I, X and M (1%), and low haplogroups frequency in pre-HV (0.7%). This study Reported absence of haplogroups V, P, Y, O, Z, Q, G, E and C.